Configurations of institutional enablers that foster inclusive entrepreneurship: A fuzzy-set qualitative comparative analysis - Aaron A. Vargas-Zeledon; Su-Yol Lee (Journal of Innovation & Knowledge (JIK), 2024)
Inclusive entrepreneurship, which represents an integrated approach to entrepreneurship and social inclusion, has increasingly received attention for its expected capacity to simultaneously foster economic growth and mitigate inequality. This study examines how the configuration of institutional enablers, which encompass several characteristics involving markets, finance, policy, education, and knowledge, fosters inclusive entrepreneurship outcomes. The results of a fuzzy-set qualitative comparative analysis using 69 country cases indicate that institutional enablers - excluding market openness - jointly affect inclusive entrepreneurship outcomes. This study provides evidence that such effects vary depending on the level of a country's economic development. As one of the first to explore the topic of inclusive entrepreneurship, this study has significant implications for academics, practitioners, and policymakers.
Keywords: M13; O17; O57; 650; Inclusive entrepreneurship; Institutional enablers; Fuzzy-set qualitative comparative analysis (fs-QCA); Global entrepreneurship monitor (gem); World economic forum (WEF)